Storage of fungi with rice (Oryza sativa)-PRH 10 and their influence on seed quality - KUMAR, DEEPAK; SINGH, K N; SHAMIM, MD; KUMAR, MAHESH; SIDDIQUI, MD WASIM; SRIVASTAVA, DEEPTI; KUMAR, SANJEEV; KUMAR, RAKESH; UPADHYAY, PRAVIN KUMAR (The Indian Journal of Agricultural Sciences, 2020)
Presence of fungi causing infestations deteriorates quality of husked and dehisced rice (Oryza sativa L.) seed. So, identifying storage conditions is crucial in food safety programs. Present study deals with isolation of fungi and their purification from rice to know the impact on seed storage quality. Four important fungi causing infestations viz. Aspergillus flavus, A. niger, Penicillium sp. and Fusarium sp. were isolated and characterized. Culture filtrate of fungi were studied on rice seed deterioration on the basis of seed germination percentage, root/shoot length, total carbohydrate, total protein content, α-amylase activity, lipoxygenase activity and storage proteins profiling by SDSPAGE. Maximum deterioration in rice seed was observed with A. flavus spores filtrate inoculated seeds followed by A. niger, Penicillium sp. and Fusarium sp., respectively. Enzyme activity of α-amylase and lipoxygenase were significantly increased with seed storage and their ageing.